2014
DOI: 10.3390/molecules190914667
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Analgesic Effects of the Marine-Derived Compound Comaparvin Isolated from the Crinoid Comanthus bennetti

Abstract: To date, no study has been conducted to explore the bioactivity of the crinoid Comanthus bennetti. Here we report the anti-inflammatory properties of comaparvin (5,8-dihydroxy-10-methoxy-2-propylbenzo[h]chromen-4-one) based on in vivo experiments. Our preliminary screening for anti-inflammatory activity revealed that the crude extract of Comanthus bennetti significantly inhibited the expression of pro-inflammatory proteins in lipopolysaccharide (LPS)-stimulated murine RAW 264.7 macrophage cells. Comaparvin iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 45 publications
(85 reference statements)
0
28
0
Order By: Relevance
“…Using this screening model, we have successfully illustrate the several marine-derived substances can produce efficacious anti-inflammatory activity in in vitro and in vivo models [1619]. Thus, screening for inhibitors of the pro-inflammatory mediators in marine natural bioactive substances is a promising avenue for drug development.…”
Section: Introductionmentioning
confidence: 99%
“…Using this screening model, we have successfully illustrate the several marine-derived substances can produce efficacious anti-inflammatory activity in in vitro and in vivo models [1619]. Thus, screening for inhibitors of the pro-inflammatory mediators in marine natural bioactive substances is a promising avenue for drug development.…”
Section: Introductionmentioning
confidence: 99%
“…The iNOS is increased in in ammatory and neuropathic pain, which promotes the synthesis of nitric oxide to induce the sensitization of peripheral or central sensory nerves and pain [35,36]. Inhibition of iNOS expression in macrophages is involved in alleviating in ammatory pain [37]. In carrageenan induced hindpaw in ammatory pain mice model, angelica dahurica can alleviate in ammatory pain by inhibiting the production of iNOS and nitric oxide in macrophages [38].…”
Section: Discussionmentioning
confidence: 99%
“…[185][186][187]; two new briarane diterpenoids briaviolides E and I (170,171), isolated from the Taiwanese soft coral Briareum violacea [188]; a new pigmented phenazine compound dermacozine H (172), isolated from the actinomycete Dermacoccus abyssi sp. nov. strain MT1.1, isolated from a Mariana Trench sediment at a depth of 10,898 m [189]; a novel sesquiterpene dysifragilone A (173), isolated from the South China Sea sponge Dysidea fragilis [190]; a new xenicane 4α-hydroxypachylactone (174), isolated from a Chinese brown alga Dictyota plectens [191]; a polyketide comaparvin (175), isolated from the Taiwanese marine crinoid Comanthus bennetti [192]; two novel eunicellin-type diterpenoids hirsutalins N and S (176, 177) and a new tocopherol-derived metabolite hirsutocospiro A (178), isolated from the Taiwanese soft coral Cladiella hirsuta [193][194][195]; a new cembranoid isosinulaflexiolide K (179), isolated from cultured Taiwanese soft corals Sinularia sandensis and Sinularia flexibilis [196]; a novel 9,11-secogorgosteroid klyflaccisteroid F (180), isolated from the Taiwaneses soft coral Klyxum flaccidum [197]; new eunicellin-type diterpenoids krempfielins N (181), Q (182), and R (183), isolated from a Taiwanese soft coral Cladiella krempfi [198,199]; a methylfarnesylquinone (184), isolated from the Taiwanese marine brown alga Homeostrichus formosana [200]; a novel steroid monanchosterol B (185), isolated from the Korean sponge Monanchora sp. [201]; a oxygenated steroid derivative (186), isolated from the Vietnamese starfish Protoreaster nodosus [202]; a new spirobisnaphthalene rhytidenone C (187), isolated from an extract of a cultured fungal endophyte Rhytidhysteron sp.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Kwan and colleagues reported that the peptide grassypeptolide A (192), isolated from the marine cyanobacterium Lyngbya confervoides, inhibited IL-2 production and proliferation of activated T cells by inhibiting the protease dipeptidyl peptidase 8, probably by binding at inner cavity of the enzyme at two distinct sites [208]. Wang and colleagues isolated a pair of novel bisheterocyclic quinolone-imidazole alkaloids (+)-and ( _ ) spiroreticulatine (193) from the South China sea sponge Fascaplysinopsis reticulata, which showed inhibition of IL-2 production by Jurkat T cells [209].…”
Section: Marine Compounds With Activity On the Immune Systemmentioning
confidence: 99%